2003
DOI: 10.1161/01.hyp.0000053448.95913.3d
|View full text |Cite
|
Sign up to set email alerts
|

Placental Insufficiency Leads to Development of Hypertension in Growth-Restricted Offspring

Abstract: Abstract-Low birth weight is a suggested risk factor for the development of hypertension. The purpose of the present study was to determine whether a model of intrauterine growth restriction produced in response to placental insufficiency in the pregnant rat was associated with marked elevations in blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
293
4
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 265 publications
(325 citation statements)
references
References 35 publications
22
293
4
4
Order By: Relevance
“…There was a trend for increased total protein levels in sham rats treated with 5 mg/kg per day ELP‐VEGF, but it is possible that degradation products of the infused protein itself are being detected in this assay. It has been widely studied that the RUPP surgery induces fetal resorption and intrauterine growth restriction of the surviving pups 72, 73, 74, 75, 76. Fetal resorption and fetal growth restriction was observed in our study as well (Table 1 and Figure S3), validating the success of the RUPP procedure in our rats.…”
Section: Resultssupporting
confidence: 87%
“…There was a trend for increased total protein levels in sham rats treated with 5 mg/kg per day ELP‐VEGF, but it is possible that degradation products of the infused protein itself are being detected in this assay. It has been widely studied that the RUPP surgery induces fetal resorption and intrauterine growth restriction of the surviving pups 72, 73, 74, 75, 76. Fetal resorption and fetal growth restriction was observed in our study as well (Table 1 and Figure S3), validating the success of the RUPP procedure in our rats.…”
Section: Resultssupporting
confidence: 87%
“…1 Perturbations of the maternal environment that lead to intrauterine growth retardation (IUGR) can have a marked impact on the grown offspring, including increased cardiovascular risk factors (eg, blood pressure and insulin resistance 1,2 ) and reduced adult life span. 3 A wide range of experimental interventions have been used to provoke developmental programming, including disturbances in maternal nutrition (eg, undernutrition and nutritional imbalances 4 ), restriction of uterine blood flow, 5 and the administration of drugs (eg, glucocorticoids 2 and NO synthase inhibitors 6,7 ).…”
mentioning
confidence: 99%
“…Because IUGR within the Western world is more likely the result of reduced uterine perfusion, 24 we have developed a model of fetal programming induced by placental insufficiency caused by hypoxia and fetal undernutrition. 25 Using this model, we previously reported that reduced uterine perfusion initiated at day 14 of gestation in the rat results in growth-restricted offspring that are hypertensive as early as 4 weeks of age. 25 Furthermore, marked elevations in mean arterial pressure (MAP) remain evident in male growth-restricted offspring at 12 weeks of age.…”
mentioning
confidence: 99%
“…25 Using this model, we previously reported that reduced uterine perfusion initiated at day 14 of gestation in the rat results in growth-restricted offspring that are hypertensive as early as 4 weeks of age. 25 Furthermore, marked elevations in mean arterial pressure (MAP) remain evident in male growth-restricted offspring at 12 weeks of age. Because increased renal sympathetic nerve activity appears to be a causal mechanism in primary hypertension, 26 we determined the role of the renal nerves in mediating the hypertension observed in adult male growthrestricted offspring, a product of placental insufficiency.…”
mentioning
confidence: 99%